2023
DOI: 10.3389/fpsyg.2022.1087528
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and prevalence of stress, anxiety, depression, and PTSD among university students during the second wave of the COVID-19 pandemic in Turkey

Abstract: This study aimed to find the prevalence of stress, anxiety, depression, and PTSD; differences according to demographic variables; and predictors of mental health problems during the second wave of the coronavirus disease (COVID-19) pandemic in Turkey. Differences in exposure to COVID-19 during the first and second waves of the pandemic among students were compared. A total of 754 students from seven universities in different parts of Turkey participated in the survey between November and December 2020. Perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…The authors focused on similar demographic and psychological characteristics to ours. More specifically, it was reported that religiosity level, marital status, year of study, gender, physical activity, COVID-19 symptoms, death of a close relative and job loss should be considered as major stressors, correlated with the psychological distress of students in Turkey [ 24 ]. These interesting observations indicate the importance of analyzing the participants’ characteristics to designate probable risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The authors focused on similar demographic and psychological characteristics to ours. More specifically, it was reported that religiosity level, marital status, year of study, gender, physical activity, COVID-19 symptoms, death of a close relative and job loss should be considered as major stressors, correlated with the psychological distress of students in Turkey [ 24 ]. These interesting observations indicate the importance of analyzing the participants’ characteristics to designate probable risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…A strict parenting style may cause children to perceive parental supervision as a barrier to communication, and youngsters who spend more time online to avoid difficult family interactions are more likely to display indicators of internet addiction [ 77 ]. However, social class psychology research has discovered that life satisfaction is positively predicted by family socioeconomic status, and better family socioeconomic status typically begets higher life satisfaction [ 79 ]. Conversely, in traditional families, the father is the main breadwinner, and students’ living expenses mainly come from their families.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the change in the essence of students' academic interactions from direct ones to indirect (mostly online) ones significantly increased psychological morbidity [42][43][44]. In this respect, many students exhibited depressive symptomatology, anxiety and sleep disturbances [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%